Dry-cured ham packaged under vacuum: nutritional evaluation - Arede, M. (2017)
Introduction: Dry-cured ham is a charcuterie product very appreciated in European countries such as Portugal, Spain and Italy. This product is generally found in the market as a whole-piece format or sliced in vacuum-packed trays. The aim of this study was to determine the moisture, fat, protein content and individual fatty acids of sliced dry-cured hams commercialized in Portugal and packaged under vacuum.